The impact of altered gut microbiota and lipid metabolism on the progression of endometrial cancer in overweight populations - Chen, Jiayu; Peng, Haochen; Shao, Yawen; Wu, Zhenzhen (Frontiers in Endocrinology, 2025)
BackgroundEndometrial cancer (EC) is one of the common malignant tumors among women, and in recent years, the role of gut microbiota in tumorigenesis has been increasingly gaining attention.Existing research has shown that the gut microbiome, establishes axis connections with multiple extra-intestinal organs. However, whether gut microbes affect the process of endometrial carcinogenesis through metabolic pathways and the specific mechanisms by which they promote the development of EC remain unclear. This study aims to explore the impact of overweight-mediated gut microbiota on the initiation or progression of EC and to assess its relationship with metabolites, thereby providing new insights for early diagnosis and treatment.MethodsIn this study, we analyzed gut microbiota differences among normal-weight, overweight EC patients, and healthy controls using 16S rRNA sequencing. Liquid chromatography-mass spectrometry (LC-MS) and KEGG analysis identified group-specific metabolites and pathways, while Spearman correlation analysis revealed associations between microbiota and metabolites.ResultsThis study revealed that in the ECMO group, the genus Megamonas exhibited the highest abundance and significant intergroup differences (H=13.46, P<0.05). Additionally, the Bacillota/Bacteroidota ratio (B/B ratio) gradually increased in the CN, ECMN, ECMO group. LEfSe analysis identified Megamonas and Amedibacillus as potential biomarkers for the ECMO group. Serum metabolomics of overweight EC patients highlighted lipid metabolism-related metabolites with the most specific expression. KEGG enrichment analysis of differential metabolites highlighted that the Glycerophospholipid metabolism and Purine metabolism pathways were notably significant in both the ECMN and ECMO groups.ConclusionThe study found significantly elevated abundance of Megamonas in the gut microbiota of overweight EC patients, which may promote EC progression by degrading inositol to enhance lipid absorption. This reveals the role of gut microbiota in EC pathogenesis through lipid metabolism regulation, providing a theoretical basis for microbiota-based diagnostic and therapeutic strategies.